Reducing Oil Dependence: A Sustainable Fiscal Strategy for Iraq - Mustafa Mahdi Abdulridha (International Journal on Economics, Finance and Sustainable Development, 2026)
Iraq possesses an oil-dominated economy, relying on over 90% of its government revenue from petroleum exports. Such reliance creates situations where extreme shifts in international oil rates lead to huge budgetary shortages, increased inflation and economic meltdowns for the economy. Iraq requires a sustainable fiscal policy to reduce its dependence on oil, to ensure long-term macro-economic stability and diversification among other sectors. The article reviews pivotal policy measures: taxation, public sector streamlining; and private sector establishment. Through improved tax collection mechanisms, a greater investment in a solid infrastructure and a global business-friendly climate, Iraq will increase non-oil revenues and encourage industrial and agricultural expansion. In addition, governance reforms along with transparency measures will be necessary to provide effective public spending and reduce corruption. It also examines practical fiscal diversification approaches undertaken by other resource-rich countries, and offers customized policy prescriptions based on Iraq's unique economic and political realities. If correctly implemented, these policies could help Iraq progress toward an economy that is more resilient, diversified, and sustainable; one that would be less susceptible to external shocks and maintain prosperity in the medium to longer term.